Potential contribution of yeast in spoilage of quail meat - Ismail, Soad Ahmed Soliman (2006)
This study was undertaken to determine the yeast population on fresh and frozen quail, and to assess its potential role in quail meat spoilage. One hundred samples 50 each of fresh and frozen quail carcasses were examined for total yeast counts, types and the frequency of the isolated yeast species. Populations of yeasts (cfulgm) ranged from 4xlO2 to 5x 105 and from 6x IO to 3xlO3 in fresh and frozen quail samples respectively. The mean values were 4.6x 103 and 6.3 x 102 in fresh and frozen quail samples respectively. A total of 131 cultures of yeasts were isolated from the examined quail samples.
Includes references.
Summary in Arabic.
Keywords: Quails; Yeasts; Meat -- Quality; Meat -- Contamination